The Names of the Last Eight Kings of the Kassite Dynasty - Brinkman, John A.
29. Enlil-nādin-šumi (Illil-nādin-šumi); 30. Kadašman-Ḫarbe (II); 31. Adad-šuma-iddina; 32. Adad-šuma-uṣur; 33. Meli-Šipak/ Meli-šiḫu; 34. Marduk-apla-iddina (II); 35. Zababa-šuma-iddina; 36. Enlil-nādin-aḫi/Enlil-šuma-uṣur.